Determinants of Premature Rupture of Membranes Among Pregnant Women Admitted to Public Hospitals in Southern Ethiopia, 2020: A Hospital-Based Case–Control Study - Habte A; Dessu S; Lukas K (Dove Medical Press, 2021)
Aklilu Habte,1 Samuel Dessu,2 Kaleegziabher Lukas3 1Department of Reproductive Health, School of Public Health, College of Medicine and Health Sciences, Wachemo University, Hosanna, Southern Ethiopia; 2Department of Public Health, College of Medicine and Health Sciences, Wolkite University, Wolkite, Southern Ethiopia; 3Department of Epidemiology, School of Public Health, College of Medicine and Health Sciences, Wachemo University, Hosanna, EthiopiaCorrespondence: Aklilu Habte Tel +251912744786Email akliluhabte57@gmail.comBackground: A gush of amniotic fluid any time before the onset of labor is known as premature rupture of the membranes (PROM). Its consequences vary from maternal and neonatal mortality and morbidity to country-wide economic loss. At the national level in general, and in the study area in particular, little is known about PROM and its determinants. Hence, this study aimed at identifying determinants of PROM among pregnant women admitted to public hospitals in Southern Ethiopia, 2020.Methods and Materials: A hospital-based unmatched case–control study was conducted on 279 pregnant women (93 cases and 186 controls) admitted to public hospitals from October 1 to 30, 2020. Pregnant women admitted to maternity wards of selected hospitals with a painless gush of fluid spilling out from the vaginal canal were considered as cases. Interviewer-administered questionnaires and data abstraction tools were used to collect data. The data were coded and entered into Epi-Data version 3.1 and exported to SPSS version 23 for analysis. The determinants of PROM were identified by applying a multivariable logistic regression analysis at a p-value < 0.05.Results: Term PROM accounted for the majority, 55 (59.2%) of cases. Previous history of abortion (AOR: 4.14, 95% CI: 2.21– 9.07), lack of ANC (AOR: 3.51; 95% CI: 1.33– 8.27), previous history of PROM (AOR: 4.91; 95% CI: 2.23– 9.82), caesarean delivery (AOR: 3.02, 95% CI: 1.24– 6,40), using of a maternal waiting room (MWR) (AOR: 0.33, 95% CI: 0.15– 0.74), and mid-upper arm Circumference (MAUC) < 23cm (AOR: 3.69, 95% CI: 1.58– 8.64) were identified as significant determinants of PROM.Conclusion: Health-care providers should work on providing adequate ANC by tracing mothers who have not received it and advising pregnant women to use MWR in the final weeks of their pregnancy. Furthermore, maternal and child health care units must place a strong focus on screening and managing the nutritional status of pregnant women. Furthermore, women with a history of abortion, caesarean section, and PROM need due attention from health care providers to mitigate the occurrence of PROM.Keywords: PROM, determinants, case-control, public hospitals, Ethiopia